External visual interface for a Nikon 6D autocollimator - Bergues, Guillermo; Ames, Guillermo; Canali, Luis; Schurrer, Clemar; Flesia, Ana (Institute of Electrical and Electronics Engineers, 2014)
The goal of this paper is to describe the potential of a visual interface applied to a Nikon 6B/6D autocollimator in order to replace human operator within a “laboratory grade” measurement. The optical interface implemented consists of a Basler HD camera attached to the autocollimator’s eyepiece, camera positioning devices, and a proprietary digital image processing package, built around Matlab environment. The whole system is used to analyze the reticle image to detect both the scale and the measuring crosshair lines at sub-pixel level. The system performance was compared in a controlled experiment against an electronic level with internationally traceable certification. The resolution of the pitch angles obtained was 10 times better than that originally obtained with the instrument. This example shows that the value of 0.02 pixels for the uncertainty associated with sub-pixel position of reticle lines is realistic, allowing for continue working on a robust interface for all angle parameters that can be measured using autocollimators.
Keywords: visual interface; camera positioning device; Matlab enviroment